INDOCTRINATION TOWARD CHINESE WOMAN IN 19TH CENTURY REFLECTED IN THE NOVEL THE SNOW FLOWER AND THE SECRET FAN BY LISA LEE: FEMINIST APPROACH. - Reisyer, Chika Ellvan; Eviyanto, Winda (LPPM Universitas Putera Batam, 2020)
Indoctrination as a form of the limit of women’s space which they cannot feel any space of theirs has been restricted because of the traditions that exist in their community. This is reflected to the novel that the researcher will analysis the snow flower and the secret fan written by Lisa Lee. It is represented by the women as the agents of the event, which is they feel that they have to do their custom tradition just to make them look valuable, and this system puts men on the highest rank in the hierarchy roles in the family. This research is done by applying the concept of Barbara Welter which is the concept of woman which said that woman’s movement is being limited by their culture and also by using descriptive qualitative method. In this novel, the indoctrination divided into four parts which is the submissiveness, domesticity, purity and piety. This snow flower and the secret fan is also a representation of feminism because The space of movement in this novel is stricted due to its patriarchal system.